Hydrochemical and Stable Isotope Characteristics of Lake Water and Groundwater in the Beiluhe Basin, Qinghai–Tibet Plateau - Jinlong Li; Wei Wang; Dahao Wang; Jiaqi Li; Jie Dong (Water, 2020)
Thermokarst lakes are a ubiquitous landscape feature that impact the thermal state, hydrological process, ecological environment, and engineering stability of the permafrost. This study established the hydrochemistry and stable isotope (δ 18 O and δD) variations of lake water and groundwater in a typical basin located in the central Qinghai–Tibet Plateau (QTP) of China. The results showed that most water samples could be classified as slightly alkaline, with high levels of salinity and hardness, while the dominant water types were HCO 3 -CO 3 and Cl types. Natural hydrochemical processes, such as mineral dissolution, cation exchange, and groundwater evaporation, had strong impacts on the groundwater chemistry in this region. Dissolution of halite and carbonate minerals causes the major reactions controlling water chemistry in this basin. Additionally, the calculation of the saturation index (SI) values suggested that aragonite, calcite, and dolomite are saturated, while halite is not. Based on the analysis of the stable isotope characteristics, atmospheric precipitation, groundwater, and meltwater from the permafrost are the major sources of thermokarst lakes. Moreover, the evaporation-to-inflow ratio (E/I) indicated that all of the lakes continuously expanded and rapidly developed. Overall, groundwater is an crucial source of lake recharge and its hydrochemical characteristics also have a certain impact on lake water quality.